Prophylactic retrorectus mesh versus no mesh in midline emergency laparotomy closure for prevention of incisional hernia (PREEMER): study protocol for a multicentre, double-blinded, randomized controlled trial. Issue 1 (28th January 2022) - Mäkäräinen, Elisa; Tolonen, Matti; Sallinen, Ville; Mentula, Panu; Leppäniemi, Ari; Ahonen-Siirtola, Mirella; Saarnio, Juha; Ohtonen, Pasi; Muysoms, Filip; Rautio, Tero
Abstract: Background: Despite the fact that emergency midline laparotomy is a risk factor for an incisional hernia, active research on hernia prevention in emergency settings is lacking. Different kinds of meshes and mesh positions have been studied in elective abdominal surgery, but no randomized controlled trials in emergency settings have been published thus far. Method: The PREEMER trial (registration number NCT04311788) is a multicentre, patient- and assessor-blinded, randomized controlled trial to be conducted in six hospitals in Finland. A total of 244 patients will be randomized at a 1 : 1 ratio to either the retrorectus mesh group, featuring a self-gripping prophylactic mesh, or to the no mesh (control) group, both closed by small-stitch 4 : 1 closure with continuous slowly absorbable monofilament suturing. The primary outcome of the PREEMER trial is the incidence of incisional hernia 2 years after surgery, which will be detected clinically and/or radiologically. Secondary outcomes are the Comprehensive Complication Index score, incidence of surgical-site infections and fascial dehiscence within 30 days of surgery; the incisional hernia repair rate and mesh- or hernia-related reoperations within the 2- and 5-year follow-ups; the incidence of incisional hernia within the 5-year follow-up; and quality of life measured by RAND-36, the Activities Assessment Scale and the PROMIS questionnaire within 30 days and 2 and 5 years from surgery. Additionally, health–economic explorative measures will be explored. Conclusion: The PREEMER trial will provide level 1 evidence on incisional hernia prevention in an emergency setting. Registration number: NCT04311788 (http://www.clinicaltrials.gov ). Registered 7 March 2020. Abstract : The PREEMER trial is a multicentre, patient- and assessor-blinded, randomized controlled trial to be conducted in six hospitals in Finland. The trial will provide level 1 evidence on incisional hernia prevention in an emergency setting.